Evaluation of hepatoprotective activity of Syringa oblata leaves ethanol extract with the indicator of glutathione S-transferase A1 - Li,Ying (2018)
Abstract The leaves of Syringa oblata Lindl., Oleaceae, had been extensively used as a folk medicine to treat various infections, heal inflammations, icteric hepatitis and acute mastitis. The study was designed to evaluate the hepatoprotective activity of S. oblata leaves ethanol extract against CCl4-induced hepatotoxicity in primary hepatocytes and mice with the indicator of glutathione S-transferase alpha 1. The hepatoprotective effects of S. oblata leaves ethanol extract were evaluated on the basis of liver histopathology and biochemical parameters as well as hepatic oxidative stress markers. The results showed that CCl4 negatively modulated biochemical parameters and liver antioxidant activities. However, the use of S. oblata leaves ethanol extract restored altered-serum biochemical parameters and liver antioxidant activities in a dose-dependent manner. Importantly, the trends in S-transferase alpha 1 were similar to alanine aminotransferase and aspartate aminotransferase level, and S-transferase alpha 1 was suggested to be a marker for the evaluation of hepatoprotective activity of S. oblata leaves ethanol extract. Histopathological examination showed that CCl4 causes significant hepatic injury relative to control group. The above findings suggested that S. oblata leaves ethanol extract has hepatoprotective effects against CCl4-induced hepatic injury and S-transferase alpha 1 may be an indicator to evaluate the protective effects of S. oblata leaves ethanol extract.